Clinical significance of cyclooxygenase-2 (COX-2) in multiple myeloma - Trojan, Andreas; Tinguely, Marianne; Vallet, Sonia; Seifert, Burkhardt; Jenni, Bettina; Zippelius, Alfred; Witzens-Harig, Mathias; Mechtersheimer, Gunhild; Ho, Anthony Dick; Goldschmidt, Hartmut; Jäger, Dirk; Boccadoro, Mario; et al. (Swiss medical weekly, 2006)
Several biological and clinical considerations suggest the involvement of cyclooxygenase-2 (COX-2), the key enzyme of prostaglandin (PG) synthesis, in the pathogenesis and progression of haematological malignancies. Despite the wealth of data concerning COX-2 expression, only limited information is available on multiple myeloma (MM). Using standard immunohistochemistry we therefore evaluated COX-2 protein expression in samples from 57 patients with a primary diagnosis of MM. Time to progression and a variety of clinicopathological features were evaluated by the Kaplan-Meier method and the Cox regression model. In addition, COX-2 expression was evaluated by staining bone marrow from healthy donors and 11 patients with MGUS. Overall, 31 MM samples (54%) expressed COX-2. Positivity for COX-2 was unrelated to stage or clinical or molecular features of the disease. However, patients with COX-2 positive tumours experienced a significantly shorter time to progression (17 vs 30 months, p = 0.037). In summary, COX-2 is frequently expressed in MM and correlates with shorter progression-free survival.
Gesehen am 15.02.2022